PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA AUGMENTED REALITY TERHADAP HASIL BELAJAR IPAS SISWA KELAS V MIS NURUL HADINA PATUMBAK - Suci Maysaroh; Imelda Free Unita Manurung; Zainuddin; Nurhairani; Laurensia Masri Perangin Angin (STKIP Subang, 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by Augmented Reality (AR) media on students’ science and social science (IPAS) learning outcomes. The study was motivated by the low learning outcomes of fifth-grade students and the limited use of innovative learning models and media. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The population consisted of all fifth-grade students at MIS Nurul Hadina Patumbak in the 2025/2026 academic year, while the sample comprised 32 students divided into an experimental class and a control class. Data were collected through learning outcome tests and analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed that the data were normally distributed and homogeneous. The independent sample t-test produced a significance value of 0.012, which was less than 0.05, indicating a significant difference between the experimental and control groups. Students taught using the CTL model assisted by AR media achieved higher learning outcomes than those taught through conventional learning. Therefore, it can be concluded that the CTL model assisted by Augmented Reality media has a significant positive effect on IPAS learning outcomes among fifth-grade students at MIS Nurul Hadina Patumbak.